Hypothalamic QRFP: Regulation of Food Intake and Fat Selection - Primeaux, S. D.; Barnes, M. J.; Braymer, H. D. (Hormone and Metabolic Research, 2013)
QRFP, a member of the RFamide-related peptide family, is a strongly conserved hypothalamic neuropeptide that has been characterized in various species. Prepro-QRFP mRNA expression is localized to select regions of the hypothalamus, which are involved in the regulation of feeding behavior. The localization of the peptide precursor has led to the assessment of QRFP on feeding behaviors and the orexigenic effects of QRFP have been detected in mice, rats, and birds. QRFP acts in a macronutrient specific manner in satiated rats to increase the intake of a high fat diet, but not the intake of a low fat diet, and increases the intake of chow in food-restricted rats. Studies suggest that QRFP’s effects on food intake are mediated by the adiposity signal, leptin, and hypothalamic neuropeptides. Additionally, QRFP regulates the expression and release of hypothalamic Neuropeptide Y and proopiomelanocortin/α-Melanocyte-Stimulating Hormone. QRFP binds to receptors throughout the brain, including regions associated with food intake and reward. Taken together, these data suggest that QRFP is a mediator of motivated behaviors, particularly the drive to ingest high fat food. The present review discusses the role of QRFP in the regulation of feeding behavior, with emphasis on the intake of dietary fat.
Keywords: high fat diet; neuropeptide Y; agouti-related peptide; arcuate nucleus; ventromedial hypothalamus